2018
DOI: 10.1103/physreve.97.032417
|View full text |Cite
|
Sign up to set email alerts
|

Encounter times of chromatin loci influenced by polymer decondensation

Abstract: The time for a DNA sequence to find its homologous counterpart depends on a long random search inside the cell nucleus. Using polymer models, we compute here the mean first encounter time (MFET) between two sites located on two different polymer chains and confined locally by potential wells. We find that reducing tethering forces acting on the polymers results in local decondensation, and numerical simulations of the polymer model show that these changes are associated with a reduction of the MFET by several … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Numerous site-specific DNA transactions such as transcription, replication, and DNA repair contribute to chromatin dynamics during the cell cycle, giving rise to chromatin dynamics at different timescales and length scales. Over the past two decades, chromatin dynamics has been investigated by tracking motions of fluorescently tagged nuclear proteins visualizing structures of interest such as nucleosomes (Xu et al 2018 ; Nagashima et al 2019 ; Ashwin et al 2019 ), single genes (Marshall et al 1997 ; Belmont and Straight 1998 ; Levi et al 2005 ; Chuang et al 2006 ; Bronstein et al 2009 ; Weber et al 2012 ; Chen et al 2013 ; Lampo et al 2016 ; Germier et al 2017 ; Amitai and Holcman 2018 ; Khanna et al 2019 ; Vivante et al 2020 ), nuclear proteins, enzymes and machineries (Misteli 2001 ; Carmo-Fonseca et al 2002 ; Darzacq et al 2007 ; Stixová et al 2011 ; Cisse et al 2013 ; Hinde et al 2014 ; Eaton and Zidovska 2020 ), and subchromosomal foci (Bornfleth et al 1999 ; Albiez et al 2006 ), as well as entire chromosome territories (Zink et al 1998 ; Edelmann et al 2001 ). Furthermore, experiments measuring fluorescence recovery after photobleaching (Abney et al 1997 ; Misteli et al 2000 ; Phair and Misteli 2000 ; Kimura and Cook 2001 ) and photoactivation (Mora-Bermúdez et al 2007 ; Wiesmeijer et al 2008 ) of nuclear proteins have revealed their peculiar kinetics.…”
Section: Dynamics Of Nucleus and Its Constituentsmentioning
confidence: 99%
“…Numerous site-specific DNA transactions such as transcription, replication, and DNA repair contribute to chromatin dynamics during the cell cycle, giving rise to chromatin dynamics at different timescales and length scales. Over the past two decades, chromatin dynamics has been investigated by tracking motions of fluorescently tagged nuclear proteins visualizing structures of interest such as nucleosomes (Xu et al 2018 ; Nagashima et al 2019 ; Ashwin et al 2019 ), single genes (Marshall et al 1997 ; Belmont and Straight 1998 ; Levi et al 2005 ; Chuang et al 2006 ; Bronstein et al 2009 ; Weber et al 2012 ; Chen et al 2013 ; Lampo et al 2016 ; Germier et al 2017 ; Amitai and Holcman 2018 ; Khanna et al 2019 ; Vivante et al 2020 ), nuclear proteins, enzymes and machineries (Misteli 2001 ; Carmo-Fonseca et al 2002 ; Darzacq et al 2007 ; Stixová et al 2011 ; Cisse et al 2013 ; Hinde et al 2014 ; Eaton and Zidovska 2020 ), and subchromosomal foci (Bornfleth et al 1999 ; Albiez et al 2006 ), as well as entire chromosome territories (Zink et al 1998 ; Edelmann et al 2001 ). Furthermore, experiments measuring fluorescence recovery after photobleaching (Abney et al 1997 ; Misteli et al 2000 ; Phair and Misteli 2000 ; Kimura and Cook 2001 ) and photoactivation (Mora-Bermúdez et al 2007 ; Wiesmeijer et al 2008 ) of nuclear proteins have revealed their peculiar kinetics.…”
Section: Dynamics Of Nucleus and Its Constituentsmentioning
confidence: 99%
“…Changes in chromatin mobility are thus a general feature of the cellular response to DSBs affecting the whole genome. Experimental and theoretical studies suggest that changes in chromatin mobility of both damaged and undamaged loci increase the probability of contact between distant loci, thus promoting the kinetics of homologous pairing ( Miné-Hattab and Rothstein, 2012 ; Guerin et al, 2016 ; Miné-Hattab et al, 2017 ; Amitai and Holcman, 2018 ).…”
Section: Msd Analyses Reveal Increased Nuclear Exploration Of Damagedmentioning
confidence: 99%
“…Second, undamaged chromatin also becomes more dynamic during DSB repair, albeit to a lesser extent than repair sites ( Figure 1B ) ( Chiolo et al, 2011 ; Krawczyk et al, 2012 ; Miné-Hattab and Rothstein, 2012 ; Seeber et al, 2013 ; Lottersberger et al, 2015 ; Strecker et al, 2016 ; Herbert et al, 2017 ; Lawrimore et al, 2017 ; Miné-Hattab et al, 2017 ; Caridi et al, 2018a ; Smith et al, 2019 ; Zada et al, 2019 ). The significance of the genome-wide increase in nuclear exploration is still under debate, but this response might increase the frequency of DNA contacts to facilitate homology search ( Gehen et al, 2011 ; Neumann et al, 2012 ; Mine-Hattab and Rothstein, 2013 ; Amitai and Holcman, 2018 ), or reflect chromatin relaxation to promote access for repair ( Kruhlak et al, 2006 ; Ziv et al, 2006 ; Seeber et al, 2013 ; Delabaere and Chiolo, 2016 ). Third, repair sites undergoing HR aggregate into larger units, or “clusters” ( Figure 1C ) ( Lisby et al, 2003 ; Aten et al, 2004 ; Kruhlak et al, 2006 ; Chiolo et al, 2011 , 2013 ; Krawczyk et al, 2012 ; Neumaier et al, 2012 ; Cho et al, 2014 ; Caron et al, 2015 ; Aymard et al, 2017 ; Caridi et al, 2018a ; Schrank et al, 2018 ; Oshidari et al, 2019a ; Waterman et al, 2019 ) (reviewed in Chiolo et al, 2013 ; Guénolé and Legube, 2017 ; Schrank and Gautier, 2019 ), likely to facilitate DSB signaling and resection, e.g., by increasing the local concentration of checkpoint and repair proteins ( Chiolo et al, 2013 ; Schrank et al, 2018 ; Kilic et al, 2019 ; Oshidari et al, 2019a ; Schrank and Gautier, 2019 ).…”
Section: Introduction: Chromatin Explores a Larger Nuclear Volume In mentioning
confidence: 99%
“…Changes in chromatin mobility are thus a general feature of the cellular response to DSBs affecting the whole genome. Experimental and theoretical studies suggest that changes in chromatin mobility of both damaged and undamaged loci increase the probability of contact between distant loci, thus promoting the kinetics of homologous pairing (Miné-Hattab and Rothstein, 2012;Guerin et al, 2016;Miné-Hattab et al, 2017;Amitai and Holcman, 2018).…”
Section: Msd Analyses Reveal Increased Nuclear Exploration Of Damaged and Undamaged Chromatin In Response To Dsbsmentioning
confidence: 99%
“…Second, undamaged chromatin also becomes more dynamic during DSB repair, albeit to a lesser extent than repair sites (Figure 1B) (Chiolo et al, 2011;Krawczyk et al, 2012;Miné-Hattab and Rothstein, 2012;Seeber et al, 2013;Lottersberger et al, 2015;Strecker et al, 2016;Herbert et al, 2017;Lawrimore et al, 2017;Miné-Hattab et al, 2017;Caridi et al, 2018a;Smith et al, 2019;Zada et al, 2019). The significance of the genome-wide increase in nuclear exploration is still under debate, but this response might increase the frequency of DNA contacts to facilitate homology search (Gehen et al, 2011;Neumann et al, 2012;Mine-Hattab and Rothstein, 2013;Amitai and Holcman, 2018), or reflect chromatin relaxation to promote access for repair (Kruhlak et al, 2006;Ziv et al, 2006;Seeber et al, 2013;Delabaere and Chiolo, 2016). Third, repair sites undergoing HR aggregate into larger units, or "clusters" (Figure 1C) (Lisby et al, 2003;Aten et al, 2004;Kruhlak et al, 2006;Chiolo et al, 2011Chiolo et al, , 2013Krawczyk et al, 2012;Neumaier et al, 2012;Cho et al, 2014;Caron et al, 2015;Aymard et al, 2017;Caridi et al, 2018a;Schrank et al, 2018;Oshidari et al, 2019a;Waterman et al, 2019) (reviewed in Chiolo et al, ...…”
Section: Introduction: Chromatin Explores a Larger Nuclear Volume In Response To Dna Damagementioning
confidence: 99%